Integration of Kansei Engineering and Nudge Based Design Thinking for Patient Comfort in Healthcare Services - Hartono, Markus; Herdiana, Wyna; Sujatmiko, Guguh; Hairunnas; Jaya, Brian Kurniawan; Parung, Christabel Annora Paramita (Institute of Research and Community Outreach - Petra Christian University, 2025)
Healthcare often struggles to obtain patient comfort and autonomy, leading to confusion, frustration, and dependency on healthcare staff. In addressing this concern, this study is conducted to propose an integrative framework of Kansei Engineering (KE) and Nudge Theory (NT) within the Design Thinking (DT). It is a novel approach called KENT-DT. Utilizing a human-centric design methodology, this study implemented semi-structured interviews and direct observations with hospitalized patients to assess their emotional responses and interactions with existing beds and hospital staff. The data disclosed some critical pain points, including lack of intuitive control, discomfort, and restricted patient autonomy in bed adjustments, which too often led to dependency on hospital staff. To address these issues, this study proposed an improved hospital bed prototype utilizing KE for patient emotional design considerations and NT to subtly encourage positive patient behaviors, such as maintaining ergonomic bed positions to prevent pressured body portions. Some features of the redesigned bed are offered, such as visual cues, intuitive control location, and ergonomic support enhancements. It is to reduce dependency on staff and increase patient autonomy. According to an evaluation by a doctor and a hospital staff member, it has been concluded that there is an expected increase in patient satisfaction and autonomy. This study brings expected implications. It suggests that integrating KE and NT in medical and hospital product design can foster a more patient-centred healthcare experience, encourage speedy recovery, and reduce staff burden. Future study is highly encouraged to implement the prototype of redesigned beds and evaluate the long-term impact of them on patient recovery. The adaptability of patients across diverse healthcare facilities may be considered as well.